Development of a disposable pyruvate biosensor to determine pungency in onions (Allium cepa L.) - Abayomi, Louise Anike; Terry, Leon A.; White, S. F.; Warner, P. J. (Elsevier, 2006)
A disposable prototype pyruvate biosensor was constructed using pyruvate oxidase immobilised on mediated meldolas blue electrodes to determine pungency in onions (Allium cepa L.). The optimum operating potential was +150 mV (versus Ag/AgCl). A strong correlation between the biosensor response and untreated onion juice of known pyruvate concentration 2–12 μmol/g fresh weight (FW) was demonstrated. The biosensor was able to differentiate between low and high pungency onions. The detection limit using 1 unit of pyruvate oxidase was 1–2 μmol/g FW. Optimum concentrations of co-factors TPP, FAD and MgSO4 comprising the enzyme cocktail were determined as being 0.04, 0.1 and 30 mM, respectively.
Keywords: Meldolas blue; Fresh produce; Quality assurance; Sweet onions